Zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in oxygen-enriched side-blown furnace and preparation method thereof

By introducing complex magnesium-aluminum cementitious agent, nano-silicon micropowder and zirconia into the oxygen-rich side blower castable, the problem of insufficient strength and stability of the existing castable is solved, and higher pressure and thermal shock performance is achieved, extending service life and reducing costs.

CN119775033APending Publication Date: 2025-04-08河南瑞泰耐火材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411842029.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The castable materials used in existing oxygen-rich side blowers have problems such as low strength at room temperature and high temperature, poor thermal shock stability and short service life.

Method used

Complex magnesium-aluminum cementitious agent, nano-silicon micro powder and zirconia were used to prepare zirconium-magnesium-aluminum-chromium spinel castable to improve its thermal shock stability, slag resistance and corrosion resistance.

Benefits of technology

It significantly improves the compressive strength, flexural strength and thermal shock stability of the castable material, extends the service life, and reduces construction and maintenance costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a zirconium magnesium aluminum chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace and a preparation method thereof. The castable is mainly composed of 50-60% high-purity magnesia sand, 22-25% fused magnesia chromium sand, 8-13% magnesia aluminum spinel, 1-5% complex magnesia aluminum binder, 1-3% zirconium silicon micropowder, 1-2% nano silicon micropowder, 1-2% chromium oxide green and 1-2% zirconium oxide; in addition, an additive accounting for 1.5-2% of the total weight of each raw material is added. Various raw materials are stirred and mixed to obtain a mud material; the obtained mud material is vibrated and formed, and the zirconium magnesium aluminum chromium sample block after forming is sequentially subjected to static demoulding, re-curing, drying and heat treatment to obtain a product. The castable prepared by the invention not only has good thermal shock stability, slag resistance, corrosion resistance, high temperature resistance and high strength performance, but also greatly improves the efficiency of construction or maintenance of the kiln, reduces the cost, and meets the use needs of the top of the oxygen-enriched side-blown furnace and other parts.
Need to check novelty before this filing date? Find Prior Art

Description

1. Technical field:

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace and a preparation method thereof. 2. Background technology:

[0002] Oxygen-enriched side-blown furnaces are widely used in the secondary lead industry. The global demand for lead resources continues to rise, and secondary lead, as an important way of resource recycling, has received more and more attention. Oxygen-enriched side-blown furnaces can convert lead waste such as waste lead-acid batteries into usable lead metal through the smelting process, which can achieve effective recycling of resources and conform to the current concept of sustainable development.

[0003] When the oxygen-enriched side-blown furnace is working, its furnace and slag chamber will often be eroded and washed by the melt, and the flue will be eroded by the splashing of slag and the scouring of dusty flue gas, and the regional temperature can reach 1400℃. Therefore, the refractory materials used in the side-blown furnace must have the characteristics of high temperature resistance, high strength, good slag resistance and good thermal shock stability. Magnesium-aluminum-chromium composite spinel bricks not only have strong high temperature performance, but also have good thermal shock stability and slag resistance and anti-penetration ability, so they are widely used in various steel and non-ferrous kilns. However, when magnesium-aluminum-chromium composite spinel bricks are used in special parts of the kiln, there will be problems such as inconvenient construction. Therefore, some composite magnesium-aluminum-chromium spinel castables have also appeared to replace magnesium-aluminum-chromium composite spinel bricks, or used in copper tundishes. Generally, the composite magnesium-aluminum-chromium spinel castable binder uses aluminate cement as a binder and conventional silicon powder. Although it can solve the problems of inconvenient construction and erosion resistance, its room temperature strength and high temperature strength are not high, the thermal shock stability is poor, and the service life is short. 3. Summary of the invention:

[0004] The technical problem to be solved by the present invention is: in view of the defects of low room temperature strength and high temperature strength, poor thermal shock stability and short service life of the existing castables used in oxygen-enriched side-blown furnaces, the present invention provides a zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace and a preparation method thereof. The zirconium-magnesium-aluminum-chromium spinel castable of the present invention adopts a complex magnesium-aluminum binder, and introduces nano-silicon powder and zirconium oxide, so that the castable not only has good thermal shock stability, slag resistance, corrosion resistance, high temperature resistance and high strength performance, but also greatly improves the efficiency of construction or maintenance of the kiln, reduces costs, and meets the use needs of the top of the oxygen-enriched side-blown furnace and other parts.

[0005] In order to solve the above problems, the technical solution adopted by the present invention is:

[0006] The invention provides a zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace. The zirconium-magnesium-aluminum-chromium spinel castable is mainly composed of 50-60% of high-purity magnesia sand as a raw material, 22-25% of fused magnesia-chrome sand, 8-13% of magnesia-aluminum spinel, 1-5% of complex magnesia-aluminum binder, 1-3% of zirconium-containing silicon powder, 1-2% of nano silicon powder, 1-2% of chromium oxide green and 1-2% of zirconium oxide, and in addition, an additive accounting for 1.5-2% of the total weight of all raw materials is added.

[0007] According to the above-mentioned zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace, the high-purity magnesia 50-60% is composed of 17-22% of 4-2mm high-purity magnesia, 15-18% of 2-0mm high-purity magnesia and 15-23% of 200-mesh high-purity magnesia powder.

[0008] According to the above-mentioned zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace, the mass percentage of magnesium in the high-purity magnesia sand is ≥96.5%.

[0009] According to the above-mentioned zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace, the 22-25% fused magnesia-chrome sand is composed of 10-15% 4-2mm fused magnesia-chrome sand and 10-15% 2-0mm fused magnesia-chrome sand; the MgO content in the fused magnesia-chrome sand is ≥65%, the Cr2O3 content is ≥20%, and the Fe2O3 is ≤10%.

[0010] According to the above-mentioned zirconium magnesium aluminum chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace, the magnesium aluminum spinel is magnesium-rich spinel with a particle size of 3.5-0.5 mm; the MgO content in the magnesium aluminum spinel is ≥65% and the Al2O3 content is ≥30%.

[0011] According to the above-mentioned zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace, the MgO content in the complex magnesium-aluminum binder is ≥45%, the Al2O3 content is ≥1.5%, and the particle size is a micropowder less than 4um (the complex magnesium-aluminum binder is a new material complexed under high temperature and high pressure using nanotechnology, and the sol formed after adding water has good bonding properties).

[0012] According to the above-mentioned zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in the oxygen-enriched side-blown furnace, the SiO2 content in the zirconium-containing silicon micropowder is ≥95%, the ZrO2 content is ≥3%, and the particle size is less than 4um; the SiO2 content in the nano-silicon micropowder is ≥99%, and the particle size is 0.15-0.2um (which can increase the strength of the castable by 50%); the chromium oxide green is an ultrafine powder with a particle size of 45um, and the Cr2O3 content in the chromium oxide green is ≥99%; the particle size of the zirconium oxide is 45um, and the purity of ZrO2 is ≥98%.

[0013] According to the above-mentioned zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace, the additive is at least one of 304# steel fiber, 446# steel fiber, sodium hexametaphosphate and sodium tripolyphosphate.

[0014] In addition, a method for preparing zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace is provided, the preparation method comprising the following steps:

[0015] 1) Weigh various raw materials according to the ratio of the zirconium magnesium aluminum chromium spinel castable according to claim 1;

[0016] 2) placing the weighed raw materials in a mixer, stirring for 3 to 5 minutes, then adding water while continuing to mix and grind for 5 to 8 minutes, wherein the total amount of water added accounts for 4.5 to 5.5% of the total weight of all raw materials, and obtaining zirconium magnesium aluminum chromium spinel castable mud for lead smelting in an oxygen-enriched side-blown furnace after mixing and grinding;

[0017] 3) The obtained mud material is placed in a mold, and vibrated on a vibration table to obtain a zirconium-magnesium-aluminum-chromium sample. After standing for 24 hours, the sample is demoulded and cured for 48 hours. After marking the sample, it is placed in a drying oven and dried at 110°C for 24 hours, and finally heat treated at 1400°C for 3 hours to obtain the product zirconium-magnesium-aluminum-chromium spinel castable.

[0018] The positive beneficial effects of the present invention are:

[0019] 1. The zirconium-magnesium-aluminum-chromium spinel castable prepared by the present invention can completely replace the magnesium-aluminum-chromium composite spinel bricks or magnesium-aluminum-chromium spinel castables in the top of the oxygen-enriched side-blown furnace and other parts; and the zirconium-magnesium-aluminum-chromium spinel castable product of the present invention has more excellent compressive strength, slag resistance and corrosion resistance, better high temperature performance and thermal shock stability, can improve construction efficiency and maintenance efficiency, and reduce costs.

[0020] 2. The zirconium magnesium aluminum chromium spinel castable prepared by the present invention introduces nano silicon powder. Compared with ordinary silicon powder, nano silicon powder can significantly improve the fluidity, sintering property, and pore filling performance of the castable, improve the structural density and strength, and enhance the corrosion resistance. Nano silicon powder forms a multi-layer protective layer at high temperature, and has good mechanical properties and high temperature and oxidation resistance.

[0021] 3. The zirconium-magnesium-aluminum-chromium spinel castable prepared by the present invention introduces zirconium-silicon powder, which can increase the fluidity of the castable, fill the pores between the castable particles, and generate a gel with the hydration product, thereby improving the density, strength and corrosion resistance of the castable.

[0022] 4. The zirconium magnesium aluminum chromium spinel castable prepared by the present invention introduces a complex magnesium aluminum binder and is a new material formed by complexation under high temperature and high pressure using nanotechnology. The sol formed after adding water has good bonding properties. After drying, the strength of the zirconium magnesium aluminum chromium spinel castable can be increased, and the castable has good load softening temperature, thermal shock stability and corrosion resistance.

[0023] 5. The product prepared by the present invention has excellent performance indicators: volume density ≥ 2.9g / cm 3 , compressive strength (110℃×24h)≥70MPa, compressive strength (1400℃×3h)≥50MPa, flexural strength (110℃×24h)≥8MPa, flexural strength (1400℃×24h)≥6MPa, linear change rate (1400℃×3h) 0~0.4%, and it has high strength, good slag resistance, anti-corrosion ability and thermal shock stability, which can fully meet the use requirements of the top of oxygen-enriched side-blown furnace and other parts. 4. Specific implementation methods:

[0024] The present invention is further described below in conjunction with embodiments to facilitate understanding of the technical solution of the present invention, but does not limit the scope of protection of the technical solution of the present invention.

[0025] In the following embodiments, the mass percentage of magnesium in the high-purity magnesia sand used is ≥96.5%; the MgO content in the fused magnesia-chrome sand is ≥65%, the Cr2O3 content is ≥20%, and the Fe2O3 is ≤10%; the magnesia-alumina spinel is a magnesium-rich spinel with a particle size of 3.5 to 0.5 mm, and the MgO content in the magnesia-alumina spinel is ≥65%, and the Al2O3 content is ≥30%; the MgO content in the complex magnesia-alumina binder is ≥45%, and the Al2O3 content is ≥1.5%, and the particle size is a micropowder less than 4 um (the complex magnesia-alumina binder is a nano-technology A new material formed by complexation under high temperature and high pressure, the sol formed after adding water has good cementing properties); the SiO2 content of zirconium-containing silicon micropowder is ≥95%, the ZrO2 content is ≥3%, and the particle size is less than 4um; the SiO2 content of nano-silicon micropowder is ≥99%, and its particle size is 0.15-0.2um (it can increase the strength of the castable by 50%); chromium oxide green is an ultrafine powder with a particle size of 45um, and the Cr2O3 content in chromium oxide green is ≥99%; the particle size of zirconium oxide is 45um, and the purity of ZrO2 is ≥98%.

[0026] Embodiment 1:

[0027] The zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace of the present invention is composed, expressed in weight percentage, of 22% of high-purity magnesia sand of 4-2 mm, 18% of high-purity magnesia sand of 2-0 mm, 17% of high-purity magnesia sand of 200 meshes, 8% of magnesia-aluminum spinel, 10% of fused magnesia-chrome sand of 4-2 mm, 12% of fused magnesia-chrome sand of 2-0 mm, 5% of complex magnesia-aluminum binder, 3% of zirconium-containing silicon micropowder, 2% of nano silicon micropowder, 1% of chromium oxide green and 2% of zirconium oxide; in addition, 304# steel fiber accounting for 1.5% of the total weight of various raw materials, 0.1% of sodium tripolyphosphate and 0.1% of sodium hexametaphosphate are added.

[0028] Embodiment 2:

[0029] The method for preparing zirconium magnesium aluminum chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace according to Example 1 of the present invention comprises the following detailed steps:

[0030] 1) Weigh various raw materials according to the ratio of zirconium magnesium aluminum chromium spinel castable described in Example 1;

[0031] 2) placing the weighed raw materials in a mixer, stirring for 5 minutes, then adding water while continuing to mix and grind for 6 minutes, adding a total of 5% of the total weight of all raw materials, and mixing and grinding to obtain zirconium magnesium aluminum chromium spinel castable mud for lead smelting in an oxygen-enriched side-blown furnace;

[0032] 3) The obtained mud material is placed in a mold, and vibrated on a vibration table to obtain a zirconium-magnesium-aluminum-chromium sample. After standing for 24 hours, the sample is demoulded and cured for 48 hours. After marking the sample, it is placed in a drying oven and dried at 110°C for 24 hours, and finally heat treated at 1400°C for 3 hours to obtain the product zirconium-magnesium-aluminum-chromium spinel castable.

[0033] The relevant performance indicators of the product prepared in this example are: volume density is 3.04g / cm 3 The compressive strength (110℃×24h) is 85MPa, the compressive strength (1400℃×3h) is 58MPa, the flexural strength (110℃×24h) is 8MPa, the flexural strength (1400℃×24h) is 6MPa, and the linear change rate (1400℃×3h) is 0.4%.

[0034] Embodiment 3:

[0035] The zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace of the present invention is composed, expressed in weight percentage, of 20% of high-purity magnesia sand of 4-2 mm, 15% of high-purity magnesia sand of 2-0 mm, 19% of high-purity magnesia sand of 200 meshes, 10% of magnesia-aluminum spinel, 10% of fused magnesia-chrome sand of 4-2 mm, 15% of fused magnesia-chrome sand of 2-0 mm, 3% of complex magnesia-aluminum binder, 3% of zirconium-containing silicon powder, 2% of nano silicon powder, 2% of zirconium oxide and 1% of chromium oxide green; in addition, 304# steel fiber accounting for 1.5% of the total weight of various raw materials, 0.1% of sodium tripolyphosphate and 0.1% of sodium hexametaphosphate are added.

[0036] Embodiment 4:

[0037] The method for preparing zirconium magnesium aluminum chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace described in Example 3 of the present invention has the following detailed steps:

[0038] 1) Weigh various raw materials according to the ratio of zirconium magnesium aluminum chromium spinel castable described in Example 3;

[0039] 2) placing the weighed raw materials in a mixer, stirring for 5 minutes, then adding water while continuing to mix and grind for 6 minutes, adding a total of 5% of the total weight of all raw materials, and mixing and grinding to obtain zirconium magnesium aluminum chromium spinel castable mud for lead smelting in an oxygen-enriched side-blown furnace;

[0040] 3) The obtained mud material is placed in a mold, and vibrated on a vibration table to obtain a zirconium-magnesium-aluminum-chromium sample. After standing for 24 hours, the sample is demoulded and cured for 48 hours. After marking the sample, it is placed in a drying oven and dried at 110°C for 24 hours, and finally heat treated at 1400°C for 3 hours to obtain the product zirconium-magnesium-aluminum-chromium spinel castable.

[0041] The relevant performance indicators of the product prepared in this example are: volume density is 3.01g / cm 3 The compressive strength (110℃×24h) is 70MPa, the compressive strength (1400℃×3h) is 50MPa, the flexural strength (110℃×24h) is 9.5MPa, the flexural strength (1400℃×24h) is 6MPa, and the linear change rate (1400℃×3h) is 0.17%.

[0042] Embodiment 5:

[0043] The zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace of the present invention is composed, expressed in weight percentage, of 17% of high-purity magnesia sand of 4-2 mm, 15% of high-purity magnesia sand of 2-0 mm, 19% of high-purity magnesia sand of 200 meshes, 13% of magnesia-aluminum spinel, 10% of fused magnesia-chrome sand of 4-2 mm, 15% of fused magnesia-chrome sand of 2-0 mm, 4% of complex magnesia-aluminum binder, 3% of zirconium-containing silicon powder, 1% of nano silicon powder, 1% of chromium oxide green and 2% of zirconium oxide; in addition, 446# steel fiber accounting for 1.5% of the total weight of various raw materials, 0.1% of sodium tripolyphosphate and 0.1% of sodium hexametaphosphate are added.

[0044] Embodiment 6:

[0045] The method for preparing zirconium magnesium aluminum chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace described in Example 5 of the present invention has the following detailed steps:

[0046] 1) Weigh various raw materials according to the ratio of zirconium magnesium aluminum chromium spinel castable described in Example 5;

[0047] 2) placing the weighed raw materials in a mixer, stirring for 5 minutes, then adding water while continuing to mix and grind for 6 minutes, adding a total of 5% of the total weight of all raw materials, and mixing and grinding to obtain zirconium magnesium aluminum chromium spinel castable mud for lead smelting in an oxygen-enriched side-blown furnace;

[0048] 3) The obtained mud material is placed in a mold, and vibrated on a vibration table to obtain a zirconium-magnesium-aluminum-chromium sample. After standing for 24 hours, the sample is demoulded and cured for 48 hours. After marking the sample, it is placed in a drying oven and dried at 110°C for 24 hours, and finally heat treated at 1400°C for 3 hours to obtain the product zirconium-magnesium-aluminum-chromium spinel castable.

[0049] The relevant performance indicators of the product prepared in this example are: volume density is 3.05g / cm 3 The compressive strength (110℃×24h) is 100MPa, the compressive strength (1400℃×3h) is 70MPa, the flexural strength (110℃×24h) is 12MPa, the flexural strength (1400℃×24h) is 6MPa, and the linear change rate (1400℃×3h) is 0.3%.

[0050] Embodiment 7:

[0051] The zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace of the present invention is composed, expressed in weight percentage, of 17% of high-purity magnesia sand of 4-2 mm, 15% of high-purity magnesia sand of 2-0 mm, 17% of high-purity magnesia sand of 200 mesh, 13% of magnesia-aluminum spinel, 10% of fused magnesia-chrome sand of 4-2 mm, 15% of fused magnesia-chrome sand of 2-0 mm, 4% of complex magnesia-aluminum binder, 3% of zirconium-containing silicon powder, 2% of nano silicon powder, 2% of chromium oxide green and 2% of zirconium oxide; in addition, 446# steel fiber accounting for 1.5% of the total weight of various raw materials, 0.1% of sodium tripolyphosphate and 0.1% of sodium hexametaphosphate are added.

[0052] Embodiment 8:

[0053] The method for preparing zirconium magnesium aluminum chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace according to Example 7 of the present invention comprises the following detailed steps:

[0054] 1) Weigh various raw materials according to the ratio of zirconium magnesium aluminum chromium spinel castable described in Example 7;

[0055] 2) placing the weighed raw materials in a mixer, stirring for 5 minutes, then adding water while continuing to mix and grind for 6 minutes, adding a total of 4.5% of the total weight of all raw materials, and mixing and grinding to obtain zirconium magnesium aluminum chromium spinel castable mud for lead smelting in an oxygen-enriched side-blown furnace;

[0056] 3) The obtained mud material is placed in a mold, and vibrated on a vibration table to obtain a zirconium-magnesium-aluminum-chromium sample. After standing for 24 hours, the sample is demoulded and cured for 48 hours. After marking the sample, it is placed in a drying oven and dried at 110°C for 24 hours, and finally heat treated at 1400°C for 3 hours to obtain the product zirconium-magnesium-aluminum-chromium spinel castable.

[0057] The relevant performance indicators of the product prepared in this example are: volume density is 3.07g / cm 3 The compressive strength (110℃×24h) is 121MPa, the compressive strength (1400℃×3h) is 72MPa, the flexural strength (110℃×24h) is 14MPa, the flexural strength (1400℃×24h) is 7.5MPa, and the linear change rate (1400℃×3h) is 0.2%.

[0058] The embodiments described above are only preferred embodiments of the present invention and are not intended to limit the scope of implementation of the present invention. Therefore, any equivalent changes or modifications made according to the structures, features and principles described in the patent scope of the present invention should be included in the scope of the patent application of the present invention.

Claims

1. A zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace, characterized in that: Expressed in weight percentage, the zirconium-magnesium-aluminum-chromium spinel castable mainly consists of 50-60% high-purity magnesia sand as raw material, 22-25% fused magnesia-chrome sand, 8-13% magnesia-aluminum spinel, 1-5% complex magnesia-aluminum binder, 1-3% zirconium-containing silicon powder, 1-2% nano silicon powder, 1-2% chromium oxide green and 1-2% zirconium oxide; in addition, an admixture accounting for 1.5-2% of the total weight of all raw materials is added.

2. The zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace according to claim 1, characterized in that: The high-purity magnesia 50-60% is composed of 17-22% of 4-2mm high-purity magnesia, 15-18% of 2-0mm high-purity magnesia and 15-23% of 200-mesh high-purity magnesia powder.

3. The zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace according to claim 1 or 2, characterized in that: The mass percentage of magnesium in the high-purity magnesia is ≥96.5%.

4. The zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace according to claim 1, characterized in that: The 22-25% fused magnesia-chrome sand is composed of 10-15% 4-2mm fused magnesia-chrome sand and 10-15% 2-0mm fused magnesia-chrome sand; the fused magnesia-chrome sand contains MgO content ≥65%, Cr2O3 content ≥20%, and Fe2O3 ≤10%.

5. The zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace according to claim 1, characterized in that: The magnesia-alumina spinel is a magnesium-rich spinel with a particle size of 3.5-0.5 mm; the MgO content in the magnesia-alumina spinel is ≥65% and the Al2O3 content is ≥30%.

6. The zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace according to claim 1, characterized in that: The complex magnesium-aluminum binder has a MgO content of ≥45% and an Al2O3 content of ≥1.5%, and a particle size of the binder is a micro powder less than 4 um.

7. The zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace according to claim 1, characterized in that: The SiO2 content of the zirconium-containing silicon micropowder is ≥95%, the ZrO2 content is ≥3%, and the particle size is less than 4um; the SiO2 content of the nano-silicon micropowder is ≥99%, and the particle size is 0.15-0.2um; the chromium oxide green is an ultrafine powder with a particle size of 45um, and the Cr2O3 content of the chromium oxide green is ≥99%; the particle size of the zirconium oxide is 45um, and the purity of ZrO2 is ≥98%.

8. The zirconium-magnesium-aluminum-chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace according to claim 1, characterized in that: The admixture is at least one of 304# steel fiber, 446# steel fiber, sodium hexametaphosphate and sodium tripolyphosphate.

9. A method for preparing zirconium magnesium aluminum chromium spinel castable for lead smelting in an oxygen-enriched side-blown furnace, characterized in that: The preparation method comprises the following steps: 1) Weigh various raw materials according to the ratio of the zirconium magnesium aluminum chromium spinel castable according to claim 1; 2) placing the weighed raw materials in a mixer, stirring for 3 to 5 minutes, then adding water while continuing to mix and grind for 5 to 8 minutes, wherein the total amount of water added accounts for 4.5 to 5.5% of the total weight of all raw materials, and obtaining zirconium magnesium aluminum chromium spinel castable mud for lead smelting in an oxygen-enriched side-blown furnace after mixing and grinding; 3) The obtained mud material is placed in a mold, and vibrated on a vibration table to obtain a zirconium-magnesium-aluminum-chromium sample. After standing for 24 hours, the sample is demoulded and cured for 48 hours. After marking the sample, it is placed in a drying oven and dried at 110°C for 24 hours, and finally heat treated at 1400°C for 3 hours to obtain the product zirconium-magnesium-aluminum-chromium spinel castable.